LEVELSTRESS RESISTANCE OF CADETS 1-3 COURSES DURING TRAINING AT THE NATIONAL ACADEMY OF INTERNAL AFFAIRS - Rymyk, V. (Rehabilitation and Recreation, 2021)
In our research, the level of stress resistance of cadets of the National Academy of Internal Affairs of the first, second and third years of study was determined. The aim of the research was to determine the level of stress resistance during training in a higher education institution for the future police officers. The study used theoretical analysis and generalization of scientific and methodological literature, pedagogical testing, methods of mathematical statistics. To determine the level of stress tolerance, we used the Holmes and Rahe test. The test form contains a list of traumatic events of everyday life for the last year, which have different emotional dimension and significance, each of which is evaluated on a 100-point scale. 159 first, second and third year cadets of the Precarpathian Faculty of the National Academy of Internal Affairs of Ivano-Frankivsk were involved in the experiment. The research showed the dynamics of stress resistance from the first to the third year of study. The results of the study show that in the second and third years cadets have a maximum and high level of stress resistance (21,74% and 65,22%, respectively) and in the first year 30% of the future police officers have a low level of stress tolerance. In general, the lack of stress resistance of first-year cadets is due to changes in living and learning conditions, deteriorating health, abandonment of old habits and daily routine and changes in financial status. Senior cadets have better physical readiness for professional activity, have undergone practical training, have good motivation which explains their high level of stress tolerance.